Makan Tanpa Distraksi: Mindfulness sebagai Kunci Aktivasi PFC dalam Pengendalian Impuls - Monica Budi Saraswati; Hana Aliyyah Lail; Safiinatun Najah; Ziyadatul Khoiroh; Ruth Natalia Susanti (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to analyze the role of mindfulness in controlling impulses while eating through practice.mindful eating. By using quantitative methods and designone group pretest-posttest, the study involved five participants who had a habit of eating with multitasking. The intervention was carried out for seven days, with measurements usingMindful Attention Awareness Scale(MAAS) and daily reflective questions. Results showed an increase in mindfulness scores from an average of 8.2 to 8.8 after the intervention, although there was variation between individuals. These results indicate thatmindful eatingcan improve self-control and strengthen activityprefrontal cortex (PFC). This study has scientific contributions in the development of mindfulness-based healthy behavior interventions and recommendations for further research.